Penerapan Model Teams Games Tournament Berbasis Board Book Audio Aural untuk Meningkatkan Keterampilan Menyimak Siswa Kelas V Sekolah Dasar - Habsari, Tama Tarina; Nurjati, Ilham Rizki; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Listening skills are a fundamental competence in Bahasa Indonesia instruction, yet in practice listening activities often take place in a passive manner and are insufficiently supported by appropriate instructional media, causing many students to struggle to maintain attention and follow the storyline of aural texts. This study aimed to describe the implementation of the Teams Games Tournament (TGT) model combined with a Board Book Audio Aural and to analyze its influence on story comprehension and cooperation among 22 fifth-grade students at SDN Boyolali. A descriptive qualitative approach with a field study design was employed, using participatory observation, field notes, documentation, quizzes, and event-sequencing tasks as data collection techniques. The findings indicate that all stages of TGT were implemented effectively and that the use of the Board Book Audio Aural in the tournament phase helped most students to listen more attentively. Groups with strong internal coordination obtained higher quiz scores and were able to reconstruct the story sequence more accurately and quickly, although several challenges—such as unstable classroom conditions and variation in students’ ability to maintain focus—still affected the learning process. Overall, the integration of TGT and Board Book Audio Aural was found to enhance students’ listening skills and collaborative interaction, thereby underscoring the importance of multimodal media and structured cooperative strategies in listening instruction at the elementary school level.